(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify (the effect of the meta-cognitive learning cycle strategy on the reflective thinking of the fifth literary grade students).To achieve the aim of the research, the researcher formulated the following two zero hypotheses:- There is no statistically significant difference at the level of significance (0.05) between the mean scores of students in reflective thinking according to the (supra-cognitive learning cycle strategy), and the mean scores of students in reflective thinking that studied the same subject according to the usual (standard) method.